Lifestyle associated morbidity among geriatric population–urban and rural comparison - Agrawal, Nipun; Imtiaz, Danish; Singh, Atul K.; Gupta, Shyam B.; Jain, Abhishek (International Journal Of Community Medicine And Public Health, 2018)
Background: The proportion of people aged over 60 years is growing faster than any other age group in almost every country which can be attributed to longer life expectancy, declining birth rates, expansion of healthcare services in quality and quantity. An individual’s choice of behaviour may be either health promoting or detrimental to health. Health is both a consequence of an individual’s lifestyle and a factor determining it but it cannot be isolated from other aspects of life. With the above background, this study was planned to report and compare lifestyle and prevalence of lifestyle associated morbidities among geriatric population of rural and urban areas in district Bareilly (UP). Methods: The present descriptive cross sectional study was conducted over a period of one year amongst families registered with UHTC and RHTC of SRMS IMS, Bareilly. All persons willing to participate aged 60 years or more were interviewed in the presence of one family member. Results: A total of 525 elderly, 263 rural and 262 urban, were surveyed. The mean age of elderly residing in the rural and urban areas are 66.21±5.97 and 67.30±5.89 respectively, eldest being 96 years old rural subject. Lifestyle of rural elderlies was healthier compared to urban subjects. 12.5% rural elderly had no apparent disease against only 7.5% urban elderly. Conclusions: Overall consumption of salt and oil consumed per person per day was found to be higher amongst the elderly residing in the urban area as compared to those in the rural area. Most of the elderly of rural area (77.57%) as well as urban area (59.92%) fall in Zone–1 i.e. with an audit score below 7. Proportion of current tobacco users and ever tobacco users were higher in the rural area (40.68% and 46.76% respectively). The proportion of subjects who were apparently healthy was higher in rural area (46.77%) than urban area (39.69%).